Antagonismo de isolados de Bacillus sobre Pyricularia grisea - Sousa, Flávia Arruda de (2011)
The rice blast caused for the fungus Pyricularia grisea is the main disease of the rice, for its control there is a large use of pesticides. The use of Bacillus spp. as agents of biological control, inside of an integrated handling, presents efficiency, in addition to security for agriculturists and at the environment. Therefore, the objective of this work was to select species of Bacillus, deriving of cities located in Maranhão - Brazil, through antagonism test in vitro and in vivo. The in vitro tests realized were the method of pairing the Circle and metabolites tests, both of them to evaluate the inhibition of mycelial growth of the P. grisea. It was also performed the conidial germination test of P. grisea. In the in vivo test, it was cultivated Spring, planted in trays, after nine days of plantation if it proceeded inoculation from the isolated of Bacillus, through the spraying of the aerial part of the plants; after colonization of the antagonist for five days, the challenger pathogen P. grisea it was inoculated, through aerial spraying of rice, the assessment of severity was performed eight days after inoculation of P. grisea estimated by severity scale of 10 degrees according to Notteghem (1981). In all the experiments, the data were submitted to Variance Analysis and means were compared by Skott-Knott test, using the software SISVAR. In pairing by the Circle test, the isolated B22‟, propitiated the biggest inhibition of the mycelial growth (57.7%) of P. grisea, differing from the other isolates. In the metabolites test, them isolated that they had presented the greater inhibitory effect were B22‟, B12, B7, B41 e B47, and the metabolites proved thermostable In the test of germination of conidial all make possible inferior germination of the witness in the two evaluated periods, except the B47 isolated, in the evaluation after 2 hours of incubation. In the in vivo test, isolates B41, B47, B12, B7 and B22' allowed a less severity of the illness. The in vivo results, confirmed the antagonistic potential of the isolated Bacillus demonstrated in the in vitro tests.